FLRW solution in bimetric theory of gravitation - Borkar, M. S.; Ameen, Abdul (International Journal of Advanced Astronomy, 2017)
We have derived FLRW line-element in Bimetric Theory of Gravitation (BTG) by solving Rosen’s field equations, and it is concluded that the geometry of our model in BTG is agreed with the geometry of FLRW model in GR. It is also realized that for the large value of t, the deceleration parameter q in our model admits the value which is close to the value at present epoch predicted by the observations of [44-48].This This shows that our FLRW model in BTG is found to be in an accelerating phase at present epoch which is not the case in GR. Other geometrical and physical aspects to the model are also studied.